Deeply cooled core of the Phoenix galaxy cluster imaged by ALMA with the Sunyaev–Zel'dovich effect. (12th March 2020) - Kitayama, Tetsu; Ueda, Shutaro; Akahori, Takuya; Komatsu, Eiichiro; Kawabe, Ryohei; Kohno, Kotaro; Takakuwa, Shigehisa; Takizawa, Motokazu; Tsutsumi, Takahiro; Yoshikawa, Kohji
Abstract: We present measurements of the thermal Sunyaev–Zel'dovich effect (SZE) toward SPT-CL J2334-4243 (the Phoenix galaxy cluster) at z=0.597 by the Atacama Large Millimeter/submillimeter Array (ALMA) in Band 3. The SZE is imaged at 5^′ ′ resolution (corresponding to the physical scale of 23\:h^-1\: kpc) within 200\:h^-1\: kpc from the central galaxy, with the peak signal-to-noise ratio exceeding 11. Combined with the Chandra X-ray image, the ALMA SZE data further allow for non-parametric deprojection of electron temperature, density, and entropy. Our method can minimize contamination by the central active galactic nucleus and the X-ray absorbing gas within the cluster, both of which greatly affect the X-ray spectrum. We find no significant asymmetry or disturbance in the SZE image within the current measurement errors. The detected SZE signal shows much higher central concentration than other distant galaxy clusters and agrees well with the average pressure profile of local cool-core clusters. Unlike in typical clusters at any redshift, the gas temperature drops by at least a factor of 5 toward the center. We identify \!\! 6 × 10^11 M_ cool gas with temperature \!\! 3\: keV in the inner 20\:h^-1\: kpc. Taken together, our results imply that the gas is indeed cooling efficiently and nearly isobarically down to this radius in the Phoenix cluster.